PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA SUB POKOK BAHASAN PERTIDAKSAMAAN LINEAR SATU VARIABEL KELAS VII A SEMESTER GANJIL SMP NEGERI 1 KEDUNGJAJANG TAHUN AJARAN 2012/2013 - Winda, W; Susanto, S; Kristiani, Arika Indah (Kadikma, 2012)
Abstract. Numbered Heads Together is a cooperative learning strategy that holds each student accountable for learning the material. The advantage of NHT (Numbered Heads Together) is that it has numbering system. Type of research was Classroom Action Research (PTK). The research subjects of was grade VII A students of SMP Negeri 1 Kedungjajang and material the chosen was one variabel linear inequality. The data collection methods used in this research were observation, interview, test, and documentation. In the first cycle, the completeness of the students learning classical outcomes was 73,33% . And the second cycle, the completeness of the students learning classical outcomes was 86,67%. The first cycle to the second cycle was 13,34%.   Key Words : NHT, Cooperative Learning. One Variabel Linear Inequality, Students learning.